Effect evaluation of artemrsinins from ethanolic extract of Artemisia cina against L3 of Haemonchus contortus on a abomasal explants technique - Higuera-Piedrahita, Rosa Isabel; López-Arellano, María Eugenia; López-Arellano, Raquel; Cuenca-Verde, César; Cuéllar-Ordaz, Jorge Alfredo (Universidad Pedagógica y Tecnológica de Colombia, 2016)
The new approach of integrated nematode control has driven to look for other alternatives that consider steadily and sustainable the environment. The aim of the present study was to obtain different ethanolic fracctions from Artemisia cina plant, using artemisinins, and to evaluate the nematicide association capacity effect with infective larvae (L3) and abomasal explant. The artemisinins from A. cina were obtained by thin layer chromatography and were evaluated on unsheathed L3 of Haemonchus contortus. The abomasal technique explants were performed for triplicate and compared as follows: three control with levamisole (7.5 mg/ml), commercial artemisinin (1 mg/ml), and distillate water, and six A. cina fracctions at 1 mg/ml each one: Ac3k, Ac3b, Ac3a, Ac3h, Ac3i and Ac4b. No significant differences between fractions of A. cina and commercial artemisinin (p>0.05) were obtained. These findings led us to conclude that there was no association capacity effect of fractions of A. cina on unsheathed L3 of H. contortus, to the abomasal tissue. It is important to continue with more studies to determine the parasitic phase in which the artemisinin viability is susceptible to be affected.